1977
DOI: 10.1021/bi00640a029
|View full text |Cite
|
Sign up to set email alerts
|

Yeast mutants blocked in removing the methyl group of lanosterol at C-14. Separation of sterols by high-pressure liquid chromatography

Abstract: Sterols of a nystatin resistant mutant of the wild type parent of Saccharomyces cerevisiae were separated by a newly developed procedure involving high-pressure liquid chromatography and were identified. The mutant contained larger amounts of squalene and lanosterol (I) than the wild type, as well as 4,14-dimethylcholesta-8,24-dien-3beta-ol (II), 4,14-dimethylergosta-8,24(28)-dien-3beta-ol (III), and 14-methylergosta-8,24(28)-dien-3beta-ol (IV), which were not hitherto found in yeast. These results indicated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
22
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 20 publications
7
22
0
Order By: Relevance
“…It is also possible that the increased acetate incorporation in squalene and lanosterol is just a consequence of a block further in the pathway. This would be similar to the situation in yeast 14-demethylation mutants in which squalene also accumulated, although only a subsequent step in the biosynthetic pathway was blocked (17). Compared with the case for C. albicans, a somewhat different response to APB treatment was observed with S. cerevisiae.…”
Section: -⌬supporting
confidence: 62%
“…It is also possible that the increased acetate incorporation in squalene and lanosterol is just a consequence of a block further in the pathway. This would be similar to the situation in yeast 14-demethylation mutants in which squalene also accumulated, although only a subsequent step in the biosynthetic pathway was blocked (17). Compared with the case for C. albicans, a somewhat different response to APB treatment was observed with S. cerevisiae.…”
Section: -⌬supporting
confidence: 62%
“…Our data indicate that once the C-14 methyl is removed, C-4 demethylation proceeds rapidly even though the resulting C-14(15) double bond is not reduced. This is in contrast to the slow removal of the C-4 methyl groups when C-14 demethylation is inhibited (16,20,23). It is evident, therefore, either that C-14 methyl sterols are not good substrates for C-4 demethylation or that C-14 demethylation inhibitors also inhibit C-4 demethylation.…”
Section: Discussionmentioning
confidence: 95%
“…The failure to remove the C-14 methyl or to reduce the C-14(15) double bond does not affect the C-24 alkylation (11,17,23). This is surprising in the case of S. cerevisiae, because this reaction normally occurs late in the ergosterol biosynthetic pathway (9).…”
Section: Discussionmentioning
confidence: 99%
“…Because the concentration dependence of growth inhibition by one of these compounds parallels the degree of inhibition of demethylation, it has been suggested that the presence of the unusual sterol biosynthetic intermediate is the cause of the antifungal properties (33). This conclusion may be questioned, since it has been found that some C-14 methyl sterols will support the growth of yeast cells (6,21,32).…”
mentioning
confidence: 99%